Development of Fatigue Life Improvement Technology of Butt Joints Using Friction Stir Processing. (19th March 2014) - Park, Jeong-Ung; An, GyuBaek; Kim, Heung-ju; Choi, Jae-hyouk
Abstract : Burr grinding, tungsten inert gas (TIG) dressing, ultrasonic impact treatment, and peening are used to improve fatigue life in steel structures. These methods improve the fatigue life of weld joints by hardening the weld toe, improving the bead shape, or causing compressive residual stress. This study proposes a new postweld treatment method improving the weld bead shape and metal structure at the welding zone using friction stir processing (FSP) to enhance fatigue life. For that, a pin-shaped tool and processing condition employing FSP has been established through experiment. Experimental results revealed that fatigue life improves by around 42% compared to as-welded fatigue specimens by reducing the stress concentration at the weld toe and generating a metal structure finer than that of flux-cored arc welding (FCAW). Hot-spot stress, structural stress, and simplified calculation methods cannot predict the accurate stress at the weld toe in case the weld toe has a smooth curvature as in the case of the FSP specimen. On the contrary, a finite element calculation could reasonably predict the stress concentration factor for the FSP specimen because it considers not only the bead profile but also the weld toe profile.